POLICY OF TEMPORARY DIRECT AID PROGRAM ANALYZED FROM WELFARE STATE CONCEPT - Athiq, Ummy (Jurnal IUS (Kajian Hukum dan Keadilan), 2014)
This study aims to identify and analyze policies BLSM program in terms of the concept of the welfare state and the various constraints in the implementation of the program in terms of substance BLSM law and legal structures as well as the proposed solution. Research normative,  approach to the law,  and the conceptual approach. To study used a normative issue primary legal materials,  secondary,  and tertiary legal materials collection techniques performed by literature and later on though and qualitatively analyzed descriptively. In an effort to carry out the mandate of the welfare state that embraces the Indonesian state as outlined in the destination country and as part of the implementation of Article 34,  paragraphs 1 and 2 of the 1945 Constitution of the Republic of Indonesia,  but on the other hand,  BLSM temporary,  short duration,  and the project is only in dealing with poverty judged to be consistent with: a) Act No. 13 of 2011 on the RI poverty Management,  b) of Law No. 11 of 2009 on Social Welfare,  c) Republic Act No. 40 of 2004 on National Social Security Persistent. Welfare state is not only trying to provide relief to the poor,  but also provide social protection for all citizens to avoid poverty.Keywords: Welfare State,  BLSM